Resilience Predicts the Trajectories of College Students’ Daily Emotions During COVID-19: A Latent Growth Mixture Model - Zhang, Li; Wang, Lei; Liu, Yuan; Zhang, Junyi; Zhang, Xiaoying; Zhao, Jingxin (Frontiers in Psychology, 2021)
The objective of this study was to examine the association between resilience and trajectories of college students’ positive and negative affect during the COVID-19 pandemic. 391 college students recruited from China completed 1-week daily on-line positive and negative affect scale, and their resilience was also measured. Latent growth mixture model was used to identify classes of grief trajectories of positive and negative affect over time, corresponding to different groups of people, and to explore the effect of resilience on these trajectories. Three latent classes of positive affect were identified: a high and increase class, a high and decrease class and a medium and stable class, while two latent classes of negative affect were found: a high and stable class and a low and decrease class. The optimism dimension of resilience showed an effect on trajectories and class membership, whereas the tenacity and strength dimensions of resilience did not. Activities that promote resilience, especially optimism should be included to improve daily emotion during the COVID-19.